2018
DOI: 10.1038/s41416-018-0246-z
|View full text |Cite
|
Sign up to set email alerts
|

Galunisertib plus gemcitabine vs. gemcitabine for first-line treatment of patients with unresectable pancreatic cancer

Abstract: Background Galunisertib is the first-in-class, first-in-human, oral small-molecule type I transforming growth factor-beta receptor (ALK5) serine/threonine kinase inhibitor to enter clinical development. The effect of galunisertib vs. placebo in patients with unresectable pancreatic cancer was determined. Methods This was a two-part, multinational study: phase 1b was a non-randomised, open-label, multicentre, and dose-escalation study; phase 2 was a randomised, placebo- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
132
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 221 publications
(137 citation statements)
references
References 18 publications
3
132
0
2
Order By: Relevance
“…The most extensively tested compound is Galunisertib (LY2157299), a small molecule that inhibits TGFBR1 kinase activity. Galunisertib in combination with gemcitabine has shown modest but significant therapeutic activity in a phase 2 clinical trial for pancreatic cancer (Melisi et al, 2018). Another phase 2 clinical trial demonstrated therapeutic responses in a subset of hepatocellular carcinoma patients treated with Galunisertib as monotherapy (Faivre et al, 2014).…”
Section: Tgf-b-based Immunotherapiesmentioning
confidence: 99%
“…The most extensively tested compound is Galunisertib (LY2157299), a small molecule that inhibits TGFBR1 kinase activity. Galunisertib in combination with gemcitabine has shown modest but significant therapeutic activity in a phase 2 clinical trial for pancreatic cancer (Melisi et al, 2018). Another phase 2 clinical trial demonstrated therapeutic responses in a subset of hepatocellular carcinoma patients treated with Galunisertib as monotherapy (Faivre et al, 2014).…”
Section: Tgf-b-based Immunotherapiesmentioning
confidence: 99%
“…Interestingly, patients who had decreased expression levels of specified blood biomarkers [e.g., alpha-fetoprotein (AFP), TGF-β1, and CDH1] had improved clinical outcomes, indicating that the effects of galunisertib might be more pronounced in patients with a poor prognosis due to elevated AFP at baseline (147). Similarly, galunisertib in combination with gemcitabine improved OS with minimal added toxicity in a phase II study on patients with locally advanced or metastatic pancreatic adenocarcinoma who were considered candidates for first-line chemotherapy with gemcitabine (146).…”
Section: Clinical Datamentioning
confidence: 99%
“…TGF-β is the central inflammatory cytokine in TME and its role in mediating EMT in different types of cancer has been extensively studied and well-established (51)(52)(53)(54)(55)(56)(57). It is known that TGF-β can have a dual role in cancer progression: it can exert an anticancer role by suppressing tumor proliferation, inducing apoptosis and cell differentiation, but it can also facilitate cancer development and metastasis (58).…”
Section: Cd4 and Cd8 T Cells Player Of The Adaptive Immune Responsementioning
confidence: 99%